2016 CNHP partners meeting - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2016)
At our 2016 Partners Meeting we discussed several themes in breakouts and a few key priorities emerged from this work. Access to data, addressing climate change, and expanding services to the conservation community were prominent priorities for CNHP that were identified. We have a new strategic plan that addresses these priorities, and for this meeting we have organized panels that will examine these topics and engage you in conversations on how we will move forward as a community.
The 2016 CNHP Partners Meeting was held on January 14, 2016 in the Grand Ballroom B, Lory Student Center, Colorado State University Campus, Fort Collins, Colorado.
Keywords: Colorado; conservation; environment